Prevalence of dysphagia in institutionalized elderly - Flávio Filipe Ferreira; Licínia Vanessa Fernandes; Isabel de Jesus Oliveira (Associação Portuguesa dos Enfermeiros de Reabilitação, 2022)
Introduction: Oropharyngeal dysphagia is defined as a set of neuromuscular changes/mechanical obstruction that make swallowing difficult, jeopardizing the safety of the airway and the person's ability to maintain their nutritional needs. Its incidence increases with age causing respiratory complications, malnutrition and dehydration. It is aimed, therefore to know the prevalence of dysphagia in institutionalized erderly people in Portugal. Methodology: Study of the prevalence of dysphagia in institutionalized elderly, using a non-probabilistic convenience sampling in five residential structures for the elderly in mainland Portugal and the islands, using the Gugging Swallowing Screen as a data collection instrument. Results: Of the 93 residents included in the study, 60,22% had dysphagia. Discussion: The prevalence of dysphagia identified is higher than the existing evidence on these data for Portugal. Conclusion: These results may have implications for the practice of health professionals who work in these institutions, especially the need to integrate nurses who are specialists in Rehabilitation Nursing for early identification and intervention, thus seeking to minimize complications.